Religion and Violence in Early American Methodism: Taking the Kingdom by Force - Norton, Brenda J. (A journal of church and state, 2011)
As a lifelong Methodist and graduate of a Methodist seminary, I found the title of Jeffrey Williams's book on early Methodism intriguing. However, do not allow the title to deceive you into thinking Williams has written a book excoriating early Methodism. Williams's use of the term violence is restricted to rhetoric, which includes images on “the use of force in order to cause injury or harm to someone or something” (p. 10). He points out that this struggle is against the forces of evil, spiritual or temporal, as interpreted by early Methodists, a conclusion with which anyone who has studied the writings of John Wesley and other early Methodist preachers can agree.